1993
DOI: 10.1016/0741-5214(93)90544-v
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress echocardiography for cardiac risk assessment before aortic surgery

Abstract: Using DSE for preoperative assessment of cardiac risk allowed us to operate on 74 of 81 patients being considered for elective aortic reconstruction, with no operative deaths and a 4.1% rate of perioperative MI. Dobutamine stress echocardiography has the ability to identify patients with asymptomatic stress-induced ischemic myocardium and its increased risk for perioperative MI (p < 0.001). Equally important, for patients with clinical indicators of CAD but without DSE-inducible ischemia, no further cardiac ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…The use of DSE in preoperative risk assessment was evaluated in 16 studies, all published since 1991 and identified by a computerized search of the English language literature (Table 8) (146,149,160,(237)(238)(239)(240)(241)(242)(243)(244)(245)(246)(247)(248)(249). The populations predominantly but not exclusively included patients undergoing peripheral vascular surgical procedures.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 99%
“…The use of DSE in preoperative risk assessment was evaluated in 16 studies, all published since 1991 and identified by a computerized search of the English language literature (Table 8) (146,149,160,(237)(238)(239)(240)(241)(242)(243)(244)(245)(246)(247)(248)(249). The populations predominantly but not exclusively included patients undergoing peripheral vascular surgical procedures.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 99%
“…Although supraventricular and ventricular arrhythmias were identified as independent risk factors for perioperative cardiac events in the Original Cardiac Risk Index, 48 subsequent studies indicated a lower level of risk. 37,90,91 The paucity of studies that address surgical risk conferred by arrhythmias limits the ability to provide specific recommendations. General recommendations for assessing and treating arrhythmias can be found in other CPGs.…”
Section: Arrhythmias and Conduction Disordersmentioning
confidence: 99%
“…Postoperative pain is associated with myocardial ischemia; however, the best practices for perioperative pain management have not been completely elucidated. 90,[350][351][352] Most of the literature focusing on perioperative myocardial events compares epidural analgesia with intravenous analgesia. Importantly, the potential efficacy of epidural analgesia depends on the local system of care.…”
Section: (Level Of Evidence: B)mentioning
confidence: 99%
“…Bei Unmöglichkeit eines Belastungs-EKGs mit dem Fahrrad oder der Armkurbel ist die mechanisch oder pharmakologisch (Dipyridamol, Dobutamin, Dobutamin mit Atropin) induzierte Stressechokardiografie indiziert, die bei neu erkannten oder sich verstär-kenden Wandbewegungsstörungen Hinweise auf ein schlechtes perioperatives Outcome liefert [27,41,50]. Dagegen konnte in einer Multivarianzanalyse, die klinisch-anamnestische Daten und Ergebnisse der Stressechokardiografie untersuchte, kein Faktor mit perioperativer Herzinsuffizienz oder Kammerflimmern assoziiert werden [17].…”
Section: Echokardiografieunclassified